Impact of Frontline Demonstration on Productivity Enhancement in Chickpea (Indian Journal of Extension Education, 2011)
Chickpea, (Cicer arietinum L.), is a drought tolerant leguminous crop grown in a large area in Madhya Pradesh covering approximately 38 percent area of the country. There is a large gap between the yield achieved in various experimental trials and that of under the farmers’ fields in the state. The major constraints responsible for this untapped yield potential are adverse weather condition and inappropriate production practices. There is a considerable scope for enhancement in crop productivity by adopting region specific suitable production technologies. 733 frontline demonstrations were conducted by KVKs in the state during 2010-11 on integrated crop management, integrated disease management, integrated nutrient management, integrated pest management and on use of improved varieties at real farm situations. Prevailing farmers’ practices were compared with these recommended practices and an average yield enhancement of 38.07, 21.9, 30.52, 27.94, and 25.99 was recorded over the yield under farmers’ practices respectively with favorable economic indicators like gross and net monetary returns and benefit: cost ratio. Farmers were also found eager to adopt the demonstrated technologies.